Surviving the grind: how young black women negotiate physical and emotional labor in urban space - McCurn, Alexis S. (Sociological Spectrum, 2020)
This study draws on nearly 2 years of field research in Central East Oakland, CA, to provide an ethnographic account of the daily experiences of poor, young, black women in urban space. Few scholars have explored the collective experiences of young women living in the inner-city and the innovative strategies they develop to navigate daily life in this setting. The accounts from young women in this study reveal the different types of formal and informal labor black women do to ensure survival in the inner-city and how they describe this daily work as the “grind.” The intersection of formal and informal labor that makes up the grind is reflected in three dimensions: the half-time hustle, underground entrepreneurship, and informal support networks. Like men in the neighborhood women must contend with underemployment, poverty and race and class isolation. I explain how black women are impacted in very specific ways by these key structural shifts and harsh structural conditions and must in turn manage constraining and contradictory gendered expectations while negotiating the grind. © 2020, © 2020 Taylor & Francis Group, LLC.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; capitalisme; environnement; intersectionnalité; milieu urbain; projet charge mentale; périodes historiques; racisme; régions géographiques; sexisme; stratégie de survie; systèmes d'oppressions; thématiques; travail; états-unis

Les mesures d'austérité et les femmes: analyse des documents budgétaires depuis novembre 2008 - Couturier, Eve-Lyne; Tremblay-Pépin, Simon; Institut de recherche et informations socio-économiques (Rapport de recherche / IRIS, 2015)
Contrairement à ce que défend le gouvernement du Québec, celui-ci mène actuellement des politiques d'austérité. Ces politiques ont croisé un certain nombre de mesures de relance que le Québec a tenté d'établir depuis la crise de 2008, mais il n'en demeure pas moins que les compressions ont été plus importantes que les investissements. Cette étude montre que si les mesures de relance ont d'abord favorisé les hommes, les mesures d'austérité, quant à elles, ont surtout affecté les femmes. Ces dernières se trouvent donc doublement perdantes vis-à-vis des mesures instaurées par le gouvernement québécois depuis la crise. Si elle diffère en termes de degré, cette situation correspond à celle qu'on a pu observer en Europe lors de la mise en place de mesures d'austérité.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; austérité; canada; capitalisme; cours; discipline; histoire et politique; inégalités; patriarcat; pol4102; premier cycle; périodes historiques; régions géographiques; science politique; science politique et droit; sexisme; sofia; systèmes d'oppressions; thématiques; travail; violences